Long term survival in 200 patients with advanced stage of colorectal carcinoma and diabetes mellitus - Bešić, Nikola (Radiology and oncology (Ljubljana), 2019)
Diabetes mellitus (DM) and DM related comorbidities may initiate difficulties during cancer specific treatment and may have an impact on cancer management and outcome. The aim of our study was to find out if DM in patients with advanced colorectal carcinoma (CRC) is associated with cancer-specific or overall survival. Patients and methods. This study included 200 consecutive patients (131 males, 69 females, mean age 63 years) with elective CRC surgery at the Institute of Oncology Ljubljana and DM was found in 39 (19.5%) of them. Even 64% of patients had Stage 3 or 4 disease, so neo-adjuvant chemotherapy (CTX) and/or radiotherapy (RT) were carried out in 59% of cases. Data about gender, age, body mass index, presence of DM, American Society of Anesthesiologists (ASA) physical status score, stage of disease and postoperative complications were collected prospectively. Cancerspecific survival and overall survival were compared by log-rank test. Results. Patients with DM had a higher ASA score, BMI, the illness marker, rate of massive bleeding, blood transfusion and longer hospital stay than those without DM. The mean follow-up period was 4.75 years. All causes mortality in patients with DM and without DM was 23% and 27%, respectively. Three-year cancer-specific survival in patients with DM and without DM was 85% and 89%, respectively (p = 0.68). Three-year overall survival in patients with DM and without DM was 82% and 84%, respectively (p = 0.63). Conclusions. The presence of DM was not associated with tumor stage, disease-specific survival or overall survival in patients with advanced CRC.
Keywords: colorectal carcinoma; diabetes mellitus; kirurgija; preživetje; rak debelega črevesa in danke; sladkorna bolezen; surgery; survival